ASSESS THE RELATIONSHIP BETWEEN SOCIAL MEDIA USAGE AND SELFESTEEM AMONG NURSING STUDENTS - Valarmathi, Dr. V.; Shaji J C, Dr. Helen; Rai, Ms. Ranjana; Dungana, Ms. Sangita; Yadav, Ms. Sonam (South Eastern European Journal of Public Health, 2025)
INTRODUCTION The pervasive influence of social media on people's lives has drawn more attention in the era of digital connectedness. As we interact with these platforms, it becomes evident that they have a significant impact on how we view ourselves. With technology always. METHODOLOGY The research method used in this study is quantitative descriptive correlational research Design. The samples were selected by purposive sampling technique. The sample size was 113 nursing students. The "Social Media Usage Scale" and the "Rosenberg Self Esteem Scale" were The instruments utilized in this study to gather data. KEY RESULTS OF THE STUDY The study findings showed that 81 (71.7%) of students had a high level, 27 (23.9%) students had moderate level and 5 (4.5%) of students had a low level of social media usage. The study findings showed that 73 (64.6%) of students had inadequate level of self-esteem, 36 (31.9%) students had moderately adequate level of self-esteem and 4(3.5%) students had adequate level of self-esteem. It is evident that pupils who use social media less have higher levels of self-esteem. Conversely, students who use social media more frequently report lower levels of self-esteem. Self-esteem, parental education, and social media use were significantly correlated (P values of 0.022 and 0.007, respectively). CONCLUSION:-The study aimed to assess the relationship between social media usage and self-esteem of nursing students studying at SRM College of Nursing, which concluded that the usage of social media decreases the self-esteem of students with 71-1% of students using social media having inadequate level (64.6%) of self-esteem.